Neurodevelopment at 2 years and umbilical artery Doppler in cases of very preterm birth after prenatal hypertensive disorder or suspected fetal growth restriction: EPIPAGE‐2 prospective population‐based cohort study. (1st October 2020) - Delorme, P.; Kayem, G.; Lorthe, E.; Sentilhes, L.; Zeitlin, J.; Subtil, D.; Rozé, J. C.; Vayssière, C.; Durox, M.; Ancel, P. Y.; Pierrat, V.; Goffinet, F.; et al.
ABSTRACT: Objective: To investigate the association between absent or reversed end‐diastolic flow (ARED) on umbilical artery Doppler ultrasound and poor neurological outcome at 2 years of age after very preterm birth associated with suspected fetal growth restriction (FGR) or maternal hypertensive disorders. Methods: The study population comprised all very preterm (22–31 completed weeks) singleton pregnancies delivered because of suspected FGR and/or maternal hypertensive disorders that had umbilical artery Doppler and 2‐year follow‐up available included in EPIPAGE‐2, a prospective, nationwide, population‐based cohort of preterm births in France in 2011. Univariate and two‐level multivariable logistic regression analyses were used to assess the association of ARED in the umbilical artery, as compared with normal or reduced end‐diastolic flow, with severe or moderate neuromotor and/or sensory disability and with an Ages and Stages Questionnaire (ASQ) score below a threshold. This was defined as a score more than 2 SD below the mean in any of the five domains, at age 2, adjusting for gestational age at delivery. ASQ is used to identify children at risk of developmental delay requiring reinforced follow‐up and further evaluation. Descriptive statistics and bivariate tests were weighted according to the duration of the inclusion periods. Results: The analysis included 484 children followed up at 2 years of age, for whom prenatal umbilical artery Doppler ultrasound was available. Among them, 8/484 (1.6%) had severe or moderate neuromotor and/or sensory disability, and 156/342 (45.4%) had an ASQ score below the threshold. Compared with normal or reduced end‐diastolic flow in the umbilical artery ( n  = 305), ARED ( n  = 179) was associated with severe or moderate neuromotor and/or sensory disability (adjusted odds ratio (OR), 11.3; 95% CI, 1.4–93.2) but not with an ASQ score below the threshold (adjusted OR, 1.2; 95% CI, 0.8–1.9). Conclusion: Among children delivered before 32 weeks of gestation due to suspected FGR and/or maternal hypertensive disorder who survived until 2 years of age, prenatal ARED in the umbilical artery was associated with a higher incidence of severe or moderate neuromotor and/or sensory disability. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.